Tren dan Keterbaharuan Teknologi Abrasive Water Jet (AWJ) Terhadap Alat Berat di Tambang Batu Bara dan Rekayasa Manufaktur Modern - Apa, Abdullah; Heryana, Ghany (Jurnal Teknologi dan Rekayasa Alat Berat, 2026)
This review analyzes research trends, technological novelty, and existing research gaps in the application of Abrasive Water Jet (AWJ) technology to heavy equipment in coal mining and related fields of modern manufacturing engineering, based on a systematic synthesis of peer-reviewed scientific literature. The study aims to identify current trends and technological advancements in Abrasive Water Jet (AWJ) applications for heavy machinery in the coal mining sector and modern manufacturing engineering, while examining the impact of innovations such as 5-axis self-aligning nozzles, AI–CFD–DEM integration, and robotic automation on coal extraction efficiency, fabrication precision of heavy equipment components, and operational sustainability. Abrasive Water Jet (AWJ) technology represents a critical technological advancement for heavy equipment in coal mining through high-precision, cold cutting of thick steel and Inconel materials used in drill bits, loader buckets, and conveyor systems. Recent innovations during 2025–2026, including ultra-high operating pressures exceeding 90,000 PSI, 5-axis self-aligning nozzles, and AI-driven nesting algorithms, have been shown to improve cutting accuracy to approximately ±0.001 inch and reduce fabrication-related downtime by 20–30% in mining heavy equipment manufacturing.